2020
DOI: 10.1136/rmdopen-2020-001240
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of pain and fatigue with health-related quality of life and work in patients with psoriatic arthritis on TNFi: results of a multi-national real-world study

Abstract: Background/ObjectiveThe incidence of pain and/or fatigue in people with psoriatic arthritis (PsA) is associated with reduced health-related quality of life (HRQoL) and the ability to work, despite modern advanced therapeutic approaches. This real-world, international study examined these relationships in patients with PsA treated with tumour necrosis factor inhibitors (TNFi).MethodsData fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…It should be noted that although there is no definite guidance regarding NSAID use, this observation may indicate that the current therapeutic strategy is insufficient. These findings are in line with data from multinational studies indicating that pain and fatigue remain significant in a proportion of patients on disease-modifying treatment [ 21 , 22 ]. These findings have several implications for practice.…”
Section: Discussionsupporting
confidence: 89%
“…It should be noted that although there is no definite guidance regarding NSAID use, this observation may indicate that the current therapeutic strategy is insufficient. These findings are in line with data from multinational studies indicating that pain and fatigue remain significant in a proportion of patients on disease-modifying treatment [ 21 , 22 ]. These findings have several implications for practice.…”
Section: Discussionsupporting
confidence: 89%
“…One recent NMA also compared therapies in terms of their efficacy against structural damage using the van der Heijde-Sharp score 83. Outcomes such as PsARC and HAQ have been associated with issues of reliability, in that the former is not fully validated and may be easily achieved, as evidenced by high placebo response rates96 and the latter may be influenced by other factors, including co-morbidities and duration of disease 97…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of fatigue in patients with PsA have been associated with greater work impairment, more work time missed, greater impairment while performing daily activities, higher pain scores, and diminished persistence of TNFi treatment [ 15 , 31 ]. Recently, a multinational real-world PsA study demonstrated that, despite TNFi treatment, substantial fatigue persisted and was significantly associated with reduced work productivity [ 32 ]. Such findings highlight the importance of managing fatigue in PsA patients, as well as the need to assess fatigue accurately and identify effective treatment options [ 13 ].…”
Section: Discussionmentioning
confidence: 99%